Theory Z and science and technology human resources development policy of Japan in 21th century - lessons suggested for Vietnam - Bao Hoa, Trieu Thi; Hoa, Nguyen Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
More than 3 decades ago, William Ouchi started writing a series of articles about how to "fix up" the shortcoming in human resources management to enhance the production capacity of US companies based on successful models of Japan. These works of Ouchi had gone beyond the framework of human resources management of businesses and territorial boundaries of the United States or Japan to become one of the classic theories of human resource development, called Theory Z, even became a philosophy in dealing with people. Center of Theory Z was the word "和" (fair) which scientifically considered between the philosophy of "feeling oriented" of the Orient combined sophisticatedly with "rationale oriented" method of the West, creating vitality in scientific, business community and policy makers. The value of Theory Z was also clearly expressed in S&T human resources development policy system in 21th century of Japan: a period where Japan had to overcome major challenges for economic growth, prosperity and sustainability. In the framework of this article, the authors related Theory Z with science and technology (S&T) human resources development policy in Vietnam, at the same time, made some suggestions with the desire that Vietnam would set up a synchronized policy system, feasible to be able to achieve the development objectives of the country with high quality human resources and an advanced S&T foundation. Code: 15091601